Healthy family education for members of the Nasyiatul Aisyiyah Branch of Gamping - Fisnandya Meita Astari; Alfisna Fajru Rohmah; Ahmad Faesol; Widia Solissa; Shofiyyah Aprianingsih; Henny Halimatul Ulya; Dilfa Sandradilla (Community Empowerment, 2023)
The family is the smallest unit of society, so the health status of the household or family determines the health status of the community. Families will be categorized as healthy families as assessed by 12 healthy family indicators. Based on observation at the Nasyiatul Aisyiyah Branch of Gamping, almost all members are aged 20-18 years and have never received health education regarding indicators of a healthy family. This community service aims to increase knowledge about healthy family indicators. The implementation method uses the target group survey method, outreach, and evaluation. The result of this community service was an increase in the knowledge of ‘Aisyiyah members regarding healthy family indicators by 87.5%.